SINERGITAS DAN ETOS KERJA PEGAWAI DALAM BINGKAI PAKET JIMAT IM3 PADA CABANG DINAS PENDIDIKAN PROVINSI JATIM WILAYAH GRESIK: CABANG DINAS PENDIDIKAN PROVINSI JATIM WILAYAH GRESIK - KISWANTO KISWANTO (Mitra Pendidikan, 2023)
The research "Employees' Synergy and Work Ethics in the Frame of the IM3 Amulet Package at the East Java Education Office in the Gresik Region" is a form of research that has never been conducted by researchers. Previous research has only focused on the issue of implementing education service policies as a policy product under the umbrella of governor policies or central government policies. This research is purely an innovation step initiated by the branch of the education office. This research is especially important when associated with the following two facts. First, based on the results of previous research studies that there is no research that describes the public service model of the education office branch which is an innovation from the educational institution. Second, there are many blurry portraits of public services carried out by government agencies. Researchers in this study to achieve research objectives used qualitative methods with a research locus at the branch of the East Java education office in the Gresik region. The aims of this study are: (1) to describe kinship patterns to build employee synergy; (2) Describe the application of JIMAT behavior in supporting the work ethic; and (3) Describe IM3 in improving the quality of education services. Data collection techniques used in this study were interviews, observation and documentation. The researcher determined key information sources (Key Informants), namely the Head of the Education Office Branch, the head of the SMK/SMA section, the Head of TU, Staff, as well as supporting information sources (supportive informants) principals, supervisors, teachers and school administrative staff. Data analysis consists of three streams of activities that occur simultaneously, namely data reduction, data presentation, and drawing conclusions. The data validation technique uses source triangulation, method triangulation, key informant review, and data base preparation. The results of the study concluded that: First, the application of a good kinship pattern will build synergy between employees who are sincere, full of integrity, and service will be effective and efficient. Second, by practicing JIMAT, organizational goals in public service will be realized with excellent quality. Third, IM3's good behavior patterns can improve the quality of public services, namely excellent education services.